Improving Underarm Serving Ability in Volleyball Games Through Target Game Approach in Grade 5 Students of SDN 127 Inpres Moncongloe - Juhanis, Juhanis; Ramli, Ramli; Rahmi, Rahmi; Hudain, Muh. Adnan; Wahyudin, Wahyudin (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of this study was to determine the improvement of the ability to serve under volleyball through the target game approach in class V SDN 127 Inpres Moncongloe, Maros Regency. This study is a quantitative study with a classroom action research (CAR) approach, with two cycles. The independent variable in this study is the target game approach while the dependent variable is the ability to serve under volleyball. The population of this study was all 5th-grade students of SDN 127 Inpres Moncongloe, Maros Regency, totalling 33 people, sampling using the total sampling technique. The research data were obtained by providing a target game approach treatment and observing the ability to serve under volleyball. The data analysis technique used was descriptive statistics with percentages. Based on the research results, the results of the 60-meter basic running movement test through the playing method can improve the learning outcomes of 5th-grade students of SDN 127 Inpres Moncongloe, Maros Regency. The improvement of the ability to serve under volleyball can be seen from the values in cycles I to II. In cycle I, the completeness value was 67%, and in cycle II it became 88%. The average value of the underhand serve ability in volleyball also increased, namely in cycle I it was 76 and in cycle II it became 80. The conclusion is that there is an increase in the underhand serve ability in volleyball through the target game approach in grade 5 students of SDN 127 Inpres Moncongloe, Maros Regency.